2021
DOI: 10.1039/d0se01194k
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the support on bifunctional one-step synthesis of methylal via methanol oxidation catalysed by Fe–Mo-based bifunctional catalysts

Abstract: In the one-step preparation of methylal from methanol, achieving high methanol conversion and high methylal yield is a huge challenge. To address this problem, in this study a new Mo:Fe(2)/CAR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
4
0
2
Order By: Relevance
“…The discussion of thermodynamics, kinetics, and reaction mechanism is carried out on the basis of previous research, so the preparation method of the catalyst is consistent with the previous preparation method. Mo‐Fe/CAR catalysts with different carriers and optimized Mo‐Fe‐based bifunctional catalysts were selected for experimental validation (see the Supplementary Material for details of the specific preparation method) 34 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussion of thermodynamics, kinetics, and reaction mechanism is carried out on the basis of previous research, so the preparation method of the catalyst is consistent with the previous preparation method. Mo‐Fe/CAR catalysts with different carriers and optimized Mo‐Fe‐based bifunctional catalysts were selected for experimental validation (see the Supplementary Material for details of the specific preparation method) 34 …”
Section: Methodsmentioning
confidence: 99%
“…Mo-Fe/ CAR catalysts with different carriers and optimized Mo-Fe-based bifunctional catalysts were selected for experimental validation (see the Supplementary Material for details of the specific preparation method). 34…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…En general, este tipo de catalizadores presentan un buen desempeño en términos de selectividad hacia formaldehido (alrededor del 94%) y conversión de metanol (alrededor del 99%). Adicionalmente, se ha observado a nivel industrial la generación de pequeñas cantidades de OME 1 como subproducto, lo que evidencia la presencia de una funcionalidad acida, la cual es susceptible de ser mejorada para incrementar la productividad de 1,1-dimetoximetano 13,26 .…”
Section: Referenciasunclassified
“…Additionally, the methyl ether peak intensity of the Fe-Mo/ZSM-5 catalyst with Si:Al = 40 was greater than that of the Fe-Mo/ZSM-5 catalyst with Si:Al = 60. In previous studies 37 (adapted from ref. 9), our team revealed that the tetrahedral coordination of Al provided Bronsted acid (B acid) sites and Lewis acid (L acid) sites on the Si-Al framework.…”
Section: In-situ Infrared Exploration Of Reaction Mechanismmentioning
confidence: 99%